2015
DOI: 10.1589/jpts.27.2661
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the dual-wall pushup plus exercise in patients with scapular dyskinesis with a winged or tipped scapula

Abstract: [Purpose] This study was performed to evaluate the clinical effect of the dual-wall pushup plus exercise in patients with scapular dyskinesis with a winged or tipped scapula. [Subject] A 32-year-old man with scapular dyskinesis participated in this study. [Methods] The subject performed the dual-wall pushup plus for 2 months, 4 days a week, for an average of 2 hours each day. The scapular dyskinesis test, linear distance of the acromion, acromion angle, and inferior scapular distance were evaluated before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…Furthermore, in SD tests, a muscle adaption in healthy overhead athletes who may develop shoulder pathologies has been discovered [115,116]. The SD test gave negative results in winged or tipped scapula after two months of rehabilitation and performing dual-wall push-up plus exercises [117]. The index of levator scapulae measures levator scapular muscle strength, and it is reliable in subjects with scapular downward rotation syndrome, rather than in those without this syndrome [118].…”
Section: Clinical Examinationmentioning
confidence: 99%
“…Furthermore, in SD tests, a muscle adaption in healthy overhead athletes who may develop shoulder pathologies has been discovered [115,116]. The SD test gave negative results in winged or tipped scapula after two months of rehabilitation and performing dual-wall push-up plus exercises [117]. The index of levator scapulae measures levator scapular muscle strength, and it is reliable in subjects with scapular downward rotation syndrome, rather than in those without this syndrome [118].…”
Section: Clinical Examinationmentioning
confidence: 99%
“…Ho et al found that massage and mobilizations-with-movement (MWM) may be useful in comparison to no treatment for short-term outcomes for shoulder dysfunction [20]. There is an abundance of studies with selective exercises for stretching and strengthening the kinetic chain and scapular muscles, which shows improvement for muscular strength or selective muscles activation while using EMG feedback systems [22,52,67]. However, although EMG provides information on the activity of the muscles, EMG data are somewhat limited regarding the interpretation of the function of the whole musculoskeletal system.…”
Section: Discussionmentioning
confidence: 99%
“…Em um estudo realizado por Yoo (2015), um paciente diagnosticado com discinesia escapular foi submetido a realização do exercício de flexão na parede, com o movimento de retração e protração escapular simultaneamente, onde foi observado que após um período de aplicação, realizou-se uma nova avaliação e constatou que a discinesia escapular deste paciente havia normalizando em seu padrão biomecanicamente alterado em determinados aspectos do acrômio, ou seja, através deste exercício pode-se produzir uma força de compressão que corrige a posição escapular anormal. É importante realizar um trabalho proprioceptivo, nas instabilidades do complexo articular do ombro, para melhorar o controle neuromuscular em posições ditas como "de risco", como a abdução e rotação externa máxima.…”
Section: Avaliação Posturalunclassified